Association between physical health and neurocognition in first-episode schizophrenia - Poole, Luke G.; Ude, Andrew A.; Perdue, Hannah M.; Bourque, Jonathon R.; Sarwani, Amber P.; Dhruve, Aman P.; Alderman, Brandon L. (Frontiers in Cognition, 2024)
Introduction: Impaired cognition is a core feature of schizophrenia that is evident early in the first episode and is frequently accompanied by compromised physical health. Although physical health confers benefits to cognition, it remains unclear whether physical activity, body mass index (BMI) and cardiorespiratory fitness are associated with neurocognition in first episode schizophrenia patients. The purpose of this study was to examine differences in stimulus categorization and motor response selection processes between first-episode schizophrenia patients compared to age-matched controls and explore associations between physical health and these stages of information processing. Methods: Fourteen young adult patients receiving care following a first episode of psychosis and a matched sample of nonpsychiatric controls completed a visual oddball task from which the P3 and LRP (lateralized readiness potential) event-related potential (ERP) components were extracted to assess stimulus categorization and response selection processes, respectively. Physical activity, aerobic fitness, and BMI were correlated with ERP measures. Results: Compared with controls, patients had lower physical activity levels and longer P3 and LRP latencies. Regardless of stimulus probability, patients had reduced accuracy and slower reaction times relative to controls. In patients, marginal associations were found between physical activity and P3 difference waveform amplitude, and BMI was negatively associated with parent P3 waveform amplitude. Discussion: The present findings suggest that cognitive impairment in first-episode schizophrenia spans both stimulus-and response-related stages of information processing, and may be targeted through physical activity interventions.